Praktik Asketisme Pra Islam dan Rekonsiliasi terhadap Islamisasi di Gunung Kumbang, Brebes, Jawa Tengah (Abad XVI-XXI M) - Sunjana, Dani; Saringendyanti, Etty; Nugrahanto, Widyo (Jayapangus Press, 2024)
Mount Kumbang, located in Ketanggungan Subdistrict, Brebes Regency, has been utilized as a site for ascetic practices since pre-Islamic times up to the present. This research aims to discuss the transition of ascetic practices due to Islamization on the slopes of Mount Kumbang from the 16th century to the present. The research focuses on the narrative of the encounter between pre-Islamic asceticism and Islamization, the forms of cultural reconciliation between pre-Islamic traditions and Islam, and how the ascetic community on Mount Kumbang has been politically portrayed in the process of Islamization. The historical method, encompassing heuristic processes, criticism, interpretation, and historiography, was employed in this research. The results demonstrate that the encounter between pre-Islamic asceticism and Islamization proceeded peacefully and was full of reconciliation. The narrative of Islamization and pre-Islamic asceticism appears in the